Interactions between Siglec-8 and endogenous sialylated cis ligands restrain cell death induction in human eosinophils and mast cells - Cao, Yun; Rische, Clayton H.; Bochner, Bruce S.; O’Sullivan, Jeremy A. (Frontiers in Immunology, 2023)
Sialic acid-binding immunoglobulin-like lectin (Siglec)-8 is a sialoside-binding receptor expressed by eosinophils and mast cells that exhibits priming status-and cell type-dependent inhibitory activity. On eosinophils that have been primed with IL-5, GM-CSF, or IL-33, antibody ligation of Siglec-8 induces cell death through a pathway involving the β2 integrin-dependent generation of reactive oxygen species (ROS) via NADPH oxidase. In contrast, Siglec-8 engagement on mast cells inhibits cellular activation and mediator release but reportedly does not impact cell viability. The differences in responses between cytokine-primed and unprimed eosinophils, and between eosinophils and mast cells, to Siglec-8 ligation are not understood. We previously found that Siglec-8 binds to sialylated ligands present on the surface of the same cell (so-called cis ligands), preventing Siglec-8 ligand binding in trans. However, the functional relevance of these cis ligands has not been elucidated. We therefore explored the potential influence of cis ligands of Siglec-8 on both eosinophils and mast cells. De-sialylation using exogenous sialidase profoundly altered the consequences of Siglec-8 antibody engagement on both cell types, eliminating the need for cytokine priming of eosinophils to facilitate cell death and enabling Siglec-8-dependent mast cell death without impacting anti-Siglec-8 antibody binding. The cell death process licensed by de-sialylation resembled that characterized in IL-5-primed eosinophils, including CD11b upregulation, ROS production, and the activities of Syk, PI3K, and PLC. These results implicate cis ligands in restraining Siglec-8 function on eosinophils and mast cells and reveal a promising approach to the selective depletion of mast cells in patients with mast cell-mediated diseases.